2021
DOI: 10.3390/children8050392
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Subcutaneous Abscess: Still a Clinical Exam-Based Diagnosis and Treatment

Abstract: Subcutaneous abscesses occur frequently in the pediatric population, yet there is great variability in the approach to diagnosis and management, partly due to opposing recommendations in the current literature and the lack of a standardized protocol for diagnosis and management among pediatric medical centers. This has led to inconsistencies by the providers, as well as the hospital clinical pathways, with regards to the appropriate management of subcutaneous abscesses. We hypothesize that the current variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The increase in skin and soft tissue infections (SSTI) including abscesses has led to a subsequent increase in incision and drainage (I&D) procedures [ 8 , 9 ]. We have previously shown that the diagnosis of pediatric subcutaneous abscesses is largely clinical and that management varies widely [ 10 ]. In a study by Singer et al evaluating patient versus provider assessment of pain, I&D was considered the second most painful procedure performed in the ED [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in skin and soft tissue infections (SSTI) including abscesses has led to a subsequent increase in incision and drainage (I&D) procedures [ 8 , 9 ]. We have previously shown that the diagnosis of pediatric subcutaneous abscesses is largely clinical and that management varies widely [ 10 ]. In a study by Singer et al evaluating patient versus provider assessment of pain, I&D was considered the second most painful procedure performed in the ED [ 11 ].…”
Section: Introductionmentioning
confidence: 99%